Corporate Value and the Role of Profitability Mediation: An Empirical Review - Ariawan (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the role of profit mediation in the relationship between capital structure and dividend policy in increasing the value of the company. This study uses a quantitative method, with secondary data collection techniques from the Indonesian Capital Market Directory (ICMD). The analysis method used Partial Least Square (PLS) with the help of the SmartPLS 3.0 application. The findings of the study show that the capital structure and dividend policy have no effect on the company's value, the capital structure has no effect on profitability, the dividend policy has an effect on profitability, profitability has an effect on the company's value, profitability mediates the effect of dividend policy on the company's value but is unable to mediate the influence of the capital structure on the company's value. Managerial implications for financial practitioners to focus more on managing and developing capital structures and dividend policies to strengthen investor involvement in achieving profitability thereby driving company value. These results also underscore the importance of strategic financial planning that aligns profitability goals with shareholder expectations and market condition.